Kajian Prospek Agroindustri Fillet Ikan Patin di Kabupaten Mesuji, Provinsi Lampung - Neti Yuliana; Sri Hidayati; Masithoh Priyantini (Jurnal Teknologi dan Industri Pertanian Indonesia, 2017)
This study aimed to identify the type of catfish  commodity based-Agroindustry that are potential to be developed in Mesuji Regency and to know the value added potential commodity processing into agro-industry products. The methods used in this research were survey and interview method. Data analysis at the research stage consists of determining the types of processed products using Analytical Hierarchy Process devices and determination of added value using Hayami method. The results showed that catfish was a potential fishery commodity to be developed in Mesuji District with an alternative processing in the form of fillets. Processing of catfish into fillet gives added value of Rp. 12,355 and profit of Rp. 10.242 per kg of raw material.